PEMBUATAN DAN ANALISIS KINERJA SISTEM THERMAL INSULATION PADA MOTOR ROKET YANG MENGGUNAKAN PROPELAN CASE-BONDED - - Sutrisno (National Institute of Aeronautics and Space - LAPAN, 2011)
Liner material of case-bonded propellant rocket motor have been made by adding some filler to the liner material composition used in free standing rocket motor. The liner was manufactured by spinning method to the rocket motor tube. The case-bonded liner performance in radial burning rocket motor was analyzed using material characteristic test result combined with rocket motor burning mechanism and free standing rocket motor static test result. The case-bonded liner materials are superior to the free standing liner because it is lighter (18,94%) and have higher heat resistance (6,75%). The application of case-bonded liner for radial burning rocket motor using single configuration propellant will be safe because the heat of propellant combustion passed through the isolator materials before the rocket motor tube. Based on the analysis it is found that the case-bonded liner can be recommended to the radial burning rocket motor using single configuration propellant. Keywords: Liner, Free standing, Case-bonded